INTERVENSI ANEMIA DEFISIENSI ZAT BESI PADA IBU HAMIL: A LITERATURE REVIEW - Ryka Kurnia Dewi; Selsa Salpahany; Kaysa Refapriliana; Dhiya Calvina; Aulia Rahmah; Ain Khairunnisa (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2022)
Pregnant women are a vulnerable group to anaemia during pregnancy. It happens because the need for iron during pregnancy increases significantly. These conditions would harm both the mother and the fetus. The prevalence of anaemia in pregnancy is high, including in Indonesia. However, comprehensive literature analysis on interventions to address the anaemia of pregnancy is limited. This literature review aims to identify interventions to treat anaemia in pregnancy from various updated sources. This literature review used CINAHL, PubMed, Science Direct, and Google Scholar databases. The keywords used were pregnancy, pregnant women, anaemia, iron deficiency, and interventions. Article criteria included full text, abstract, and title appropriate to the topic. The total number of articles analyzed based on search results are 22 articles. Most research locations are in developing countries, but none in Indonesia. Interventions to treat the anaemia of pregnancy include administering Fe tablets, Fe tablets and additives, fish oil, CSB Plus, Vitamin D, and Vitamin D3. Intervention using Fe, either alone or in combination, was effective in treating anaemia in pregnancy, although there are pregnant women who experience digestive side effects. Applying several interventions to deal with anaemia in pregnancy Intervention research on anaemia in pregnancy can be used in Indonesia.